2020
DOI: 10.3389/fpsyg.2019.03090
|View full text |Cite
|
Sign up to set email alerts
|

An Item-Level Analysis for Detecting Faking on Personality Tests: Appropriateness of Ideal Point Item Response Theory Models

Abstract: How to detect faking on personality measures has been investigated using various methods and procedures. As previous findings are mixed and rarely based on ideal point item response theory models, additional research is needed for further exploration. This study modeled the responses of personality tests using ideal point method across instructed faking and honest responding conditions. A sample of undergraduate students participated the within-subjects measures to examine how the item location parameter deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Very few studies have examined the issue of aberrant data under an unfolding model context. Liu and Zhang (2020) investigated the appropriateness of ideal point models for detecting faking on personality measures (as opposed to honest responding). Results indicated that fitting the GGUM to the data under conditions where faking was present resulted in shifts in item location parameter estimates, demonstrating that faking could increase or decrease personality factor scores reflecting conscientiousness and neuroticism.…”
Section: Impacts Of Aberrant Respondingmentioning
confidence: 99%
“…Very few studies have examined the issue of aberrant data under an unfolding model context. Liu and Zhang (2020) investigated the appropriateness of ideal point models for detecting faking on personality measures (as opposed to honest responding). Results indicated that fitting the GGUM to the data under conditions where faking was present resulted in shifts in item location parameter estimates, demonstrating that faking could increase or decrease personality factor scores reflecting conscientiousness and neuroticism.…”
Section: Impacts Of Aberrant Respondingmentioning
confidence: 99%
“…Other statistical or methodological efforts to mitigate bias include adding assessments to measure social desirability itself, employing situational judgement tests to assess personality or behavioral tendencies, evaluating bias using item response theory techniques, or utilizing measures such as the Social Desirability Scale (SDS) [48][49][50]. However, a recent meta-analysis by Lanz et al, suggested the traditional SDS may provide little to no benefit in measuring either bias or a desirability trait [51].…”
Section: Challenge: Capturing Accurate Data In Self-report Collection...mentioning
confidence: 99%
“…It is important for researchers to be able to detect varying types of aberrant responses and to be aware of the potential adverse effects they may have on datasets and analyses. Because of the limited research available on the use of person-fit statistics with ideal point response data, researchers have recommended that studies investigate their use with unfolding frameworks (Drasgow et al, 2010;Lee et al, 2014;J. Liu & Zhang, 2020;Polak et al, 2012;Tendeiro, 2017).…”
Section: Purposementioning
confidence: 99%